Analysis of Choosing Quality and Character the Principal Canditate - Ali Taufik (Universitas Muhammadiyah Enrekang, 2022)
Abstract This research includes our empirical experience and then looks at the phenomena that exist about developing the quality of education and leadership character, the purpose of research to contribute to the world of education is how to choose leaders, leadership characters who have a vision and mission in improving the culture of education quality and evaluation ability. This research is universal, for leadership at the elementary school or college level. The main problem in this study concerns the leadership criteria of the institution / school, both regarding the character, mentality of the leader and the ability to do managerial in the school / institution being led. The method used in this study is a descriptive qualitative phenomenological model, because the authors consider this to be a phenomenon at the moment. The study was conducted around 4 months (16 weeks), with 5 school leaders being asked to participate during the study. , the results of the analysis of this study there are five important phases in choosing leadership in institutions / schools. For more comprehensive research, it is invited to use a qualitative or quantitative approach, to get novelty.